Analisis Profitabilitas Budidaya Cabai Merah Besar Di Kabupaten Lombok Timur - FR, Aeko Fria Utama; Suparyana, Pande Komang (LPPM Universitas Malikussaleh - Indonesia, 2023)
The purpose of this study was to determine the profitability level of large red chili cultivation in East Lombok Regency, determine the feasibility of large red chili cultivation in East Lombok Regency and find out the various obstacles to large red chili cultivation in East Lombok Regency. The research method uses descriptive method. The research sample was taken through purposive sampling. Types of qualitative data and quantitative data with primary and secondary data sources. Analysis of the data used is the analysis of profitability, feasibility of large red chili cultivation and analysis of constraints. The results showed that the Profitability value of 350% exceeded the ROI criteria of 50%, which means that the profit level of large-scale red chili is high or profitable. The feasibility of large-scale red chili cultivation in Pringgasela is considered feasible if the R/C ratio is 4.50 or greater than 1. The constraints faced by large-scale red chilies in East Lombok Regency are pest attacks, disease attacks and capital. al.